Genetically Encoded Biotin Analogues: Incorporation and Application in Bacterial and Mammalian Cells. (26th June 2019) - Hohl, Adrian; Mideksa, Yonatan G.; Karan, Ram; Akal, Anastassja; Vogler, Malvina; Groll, Michael; Rueping, Magnus; Lang, Kathrin; Feige, Matthias J.; Eppinger, Jörg
Abstract: The biotin–streptavidin interaction is among the strongest known in nature. Herein, the site‐directed incorporation of biotin and 2‐iminobiotin composed of noncanonical amino acids (ncAAs) into proteins is reported. 2‐Iminobiotin lysine was employed for protein purification based on the pH‐dependent dissociation constant to streptavidin. By using the high‐affinity binding of biotin lysine, the bacterial protein RecA could be specifically isolated and its interaction partners analyzed. Furthermore, the biotinylation approach was successfully transferred to mammalian cells. Stringent control over the biotinylation site and the tunable affinity between ncAAs and streptavidin of the different biotin analogues make this approach an attractive tool for protein interaction studies, protein immobilization, and the generation of well‐defined protein–drug conjugates. Abstract : Controlled interactions : Genetically encoded biotin and 2‐iminobiotin lysine provide stringent control over the site of modification and stoichiometry. Well‐defined biotinylated proteins can potentially simplify protein investigation, protein immobilization, and the production of protein–drug conjugates through the strong interaction to streptavidin.